2006
DOI: 10.1177/0278364906067543
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Phase-Based Gain Modulation with Designer-Chosen Switch Functions

Abstract: Phase-Based Gain-Modulation (PBGM) control is realized by modulating controller gains in response to the phase of the system state or tracking error. PBGM controllers have been applied to robotic hands, parallel manipulators and flexible mechanisms to give increased damping, reduced tracking error and friction compensation.A novel method is presented to establish Lyapunov stability for PBGM control. Prior PBGM stability results incorporated a constraint which limited the range of provably stable systems. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…The experimental results (right part) are obtained under realistic scanning set-points, feedforward control design, and disturbances and yield error responses in the same order of magnitude as in the simulations. 1 This is in favor of the choice in (46). Nevertheless, the results obtained from simulation cannot be compared directly with the results obtained from measurement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental results (right part) are obtained under realistic scanning set-points, feedforward control design, and disturbances and yield error responses in the same order of magnitude as in the simulations. 1 This is in favor of the choice in (46). Nevertheless, the results obtained from simulation cannot be compared directly with the results obtained from measurement.…”
Section: Resultsmentioning
confidence: 99%
“…Given the linear feedback design with plant P and nominal (linear) controller C fb , the nonlinear (switching) controller consists of loop-shaping filters F 1 with inputũ, weighting filters F 2 with inputỹ, and switching function y´/(y) with input y and output u(y) = À/(y)y, see also (1). The plant output z, disturbances d, and reference r form the inputỹ viaỹ ¼ r þ dÀ z.…”
Section: Lur'e Type Switching Control Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…To balance this trade-off in a more desirable manner, it has been shown that variable-gain control (also called N-PID control) can be effective [6][7][8][9][10][11][12]. In these references, it has been shown that the variable-gain controllers have the capability of outperforming linear controllers.…”
Section: Introductionmentioning
confidence: 99%
“…In N-PID control, see also [4], [5], [6], the controller gain is adapted according to the (estimated) servo signals at hand. This generally gives more flexibility in dealing with position-dependent disturbances but the problem of noise amplification under high-gain feedback remains.…”
Section: Introductionmentioning
confidence: 99%